2014
DOI: 10.1186/1471-2296-15-75
|View full text |Cite
|
Sign up to set email alerts
|

Primary care referrals of patients with potentially serious diseases to the emergency department or a quick diagnosis unit: a cross-sectional retrospective study

Abstract: BackgroundIn Spain, primary healthcare (PHC) referrals for diagnostic procedures are subject to long waiting-times, and physicians and patients often use the emergency department (ED) as a shortcut. We aimed to determine whether patients evaluated at a hospital outpatient quick diagnosis unit (QDU) who were referred to ED from 12 PHC centers could have been directly referred to QDU, thus avoiding ED visits. As a secondary objective, we determined the proportion of QDU patients who might have been evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Bosch et al [ 40 ] published a paper on referrals from GPs to a quick diagnostic unit (QDU) similar to the one described in this paper, but their aim was different from ours. The study showed that 30 % of the patients referred directly to the QDU had cancer compared to the 16 % found in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bosch et al [ 40 ] published a paper on referrals from GPs to a quick diagnostic unit (QDU) similar to the one described in this paper, but their aim was different from ours. The study showed that 30 % of the patients referred directly to the QDU had cancer compared to the 16 % found in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Data from the UK have shown that 11 % of the patients referred to the ordinary urgent referral pathways were diagnosed with cancer [ 22 ]. Apart from the study by Bosch et al [ 40 ], we are unaware of any published studies examining and quantifying GP referrals to NSSC-CPPs and related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lengthy waits in diagnostic workups owe to insufficiencies in outpatient services, with diagnosis in such settings being unfeasible, even when quick investigations for suspected cancer are necessary [ 14 16 ]. Because current referral procedures for diagnosis and specialized care in primary healthcare centers (PCCs) are prolonged, especially in public health systems such as the Spanish one, PCC physicians commonly refer patients with suspected serious diseases to the emergency department (ED) with the hope to gain quick access to examinations via hospitalization [ 12 , 13 , 17 , 18 ]. Alternatively, patients are free to pay for diagnostic tests such as a CT scan or MRI using a private provider [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although still little known today, this type of units, run by internists, nurses, and secretarial staff, have been established in Europe, and they have been principally studied in Spain [ 1 , 2 , 4 , 12 15 , 17 , 18 , 20 24 ]. The advantages over conventional hospitalization are numerous: in addition to ensuring an early diagnosis, QDUs avoid hospital-related morbidity, decrease ED referrals from PCCs and decongestion overcrowded ED, and help decrease unnecessary health costs of traditional hospitalization without lowering the quality of diagnostic practice and patient care [ 2 , 12 , 14 , 17 , 18 , 21 24 ]. Yet for QDUs to succeed, the following requirement are expected to be met: 1) clear pre-established referral criteria; 2) patients should be well enough to attend outpatient appointments for visits and diagnostic tests; 3) their first visit has to occur as soon as possible after referral; and 4) they should have preferential access to diagnostic tests [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In settings where there are weak referral structures, due to inappropriate referral practices, hospital level maternal and new-born mortality is often higher (4). Ineffective referral systems result in negative patient experiences, unnecessary high costs and are a burden on health system (9). The appropriateness of the referrals can be de ned by their distinct attributes -referral necessity, referral destination and referral quality (10).…”
Section: Introductionmentioning
confidence: 99%